European Trade – Where is Going? Retail Entertainment - JELEV, Viorica (Journal of Economic Development, Environment and People, 2017)
As competition grows, brand manager imagination needs to work, and sales growth solutions need to focus on customer focus attention. It is a difficult task if all brands offer discounts in the malls they are in, and the announcement of differentiation is put to the attention of specialists who offer solutions for fun of any kind for the clients. The article aims to present the evolution of world trade in recent years and the various ways of diversion invented by retailers to keep customers in store chains longer for them to buy more. I will also present the off-line consumer profile, as found in the specialty studies and the adaptation of the entertainment methods according to these shoper typologies. The conclusion of this article will focus on what the link between entertaiment and retail is, the new concept of RETAILTAIMENT that leads to increased sales and profits of economic agents.